A Clean Economic Dispatch of PV Energy Storage Connected to Grid Based on LHS-SR-GAMS Technology - Liu Jiang-Tao; Wang Hai-Yun; Luo Jian-Chun; Luo Qing; Chen Xing (Institute of Advanced Engineering and Science, 2014)
PV output uncertainty, the PV scheduling problem has become urgent. The combined energy storage and PV can solve effectively the problem. We established the joint energy-saving economic scheduling model on PV- Storage generation, which mainly included the penalty model about PV positive deviation output and the penalty model about PV negative deviation output and